2013
DOI: 10.1080/01652176.2013.782119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of black cumin seed (Nigella sativaL.) on performance and immune system in newly evolved crossbred laying hens

Abstract: Background: A limited number of studies have tested the effect of diets supplemented with black cumin seed (BCS) on the performance of laying hen. Objective: To determine the effects of various levels of dietary BCS on the performance of laying hen. Birds and methods: Three hundred 40-week-old rural Leghorn (White Leghorn males X F1 females of Fayoumi male X Rhode Island Red female) crossbred hens were randomly assigned to four groups with five replicates of 15 birds each (75 laying hens per group), and fed di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 30 publications
5
17
1
2
Order By: Relevance
“…The dietary inclusion of NFA and FA significantly increased the egg weight. This finding agrees with those observed by using fennel and cumin seed to increase egg weight (Aydin et al, 2008;Yalcin et al, 2009;Khan et al, 2013;Abou-Elkhair et al, 2018). Conversely, a high inclusion of A. annua leaves did not significantly increase egg weight, but dramatically decreased FCR (Baghban-Kanani et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The dietary inclusion of NFA and FA significantly increased the egg weight. This finding agrees with those observed by using fennel and cumin seed to increase egg weight (Aydin et al, 2008;Yalcin et al, 2009;Khan et al, 2013;Abou-Elkhair et al, 2018). Conversely, a high inclusion of A. annua leaves did not significantly increase egg weight, but dramatically decreased FCR (Baghban-Kanani et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In present study least survival rate (33%) was noted in group2 (positive control), while highest was noted in group added ribavirin (83%), followed by Nigella group (75%) ( Table.1). Our these results corroborate with Khan et al (2013) who also reported decreased mortality rate in laying hens using Nigella sativa. Likewise, Omer et al (2014) reported 80 % survival rate, when Ribavirin drug was used in NDV infection.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, Nigella sativa showed strong positive effects and varying degree of hypertrophy of various organs and accretion of lymphocytes in liver and other lymphatic organs ensuring elevated resistance against NDV as also conferred by Khan et al (2013), that Nigella sativa have the ability to increase and modulate body musculature and immunity (Table. 2). This high degree of activity may be due to the presence of some active components such as, thymoquinone that produces remarkable effects against virus.…”
Section: Discussionmentioning
confidence: 74%
“…Almost all previous experimental studies in animals [23,24,26,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][79][80][81], but one [25], showed a reduction in LDL-C after NS supplementation. Consistently, small clinical studies confirmed a significant LDL-C reduction after the consumption of NS in both healthy individuals [27] and dysmetabolic patients [28,29,45].…”
Section: Discussionmentioning
confidence: 99%